2009
DOI: 10.1111/j.1365-2648.2008.04878.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing practice, knowledge, attitudes and perceived barriers to evidence‐based practice at an academic medical center

Abstract: Aim. This paper is a report of a study describing nurses' practices, knowledge, and attitudes related to evidence-based nursing, and the relation of perceived barriers to and facilitators of evidence-based practice.Background. Evidence-based practice has been recognized by the healthcare community as the gold standard for the provision of safe and compassionate healthcare. Barriers and facilitators for the adoption of evidence-based practice in nursing have been identified by researchers.Healthcare organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
438
5
38

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(529 citation statements)
references
References 30 publications
48
438
5
38
Order By: Relevance
“…In the equivalence assessment, agreement for items 1 and 14 was 57%; item 18, 71% and 85% for items 3,4,7,9,12,16,19,20,23,28 and 29. The suggestions were analyzed in a discussion meeting with the researcher, the advisor, and the members of the research group on cultural adaptation of measurement instruments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the equivalence assessment, agreement for items 1 and 14 was 57%; item 18, 71% and 85% for items 3,4,7,9,12,16,19,20,23,28 and 29. The suggestions were analyzed in a discussion meeting with the researcher, the advisor, and the members of the research group on cultural adaptation of measurement instruments.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted with nurses, of various levels of training, in California also found the highest average score in this area. (12) The lowest mean scores were found in the domain related to knowledge and skills associated to EBP. The items questioned the frequency of literature review and the elaboration of research questions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…표준지침으 로 통용되는 CDC의 감염관리 관련 근거기반 실무지침에 관한 지식의 경우, 중환자실 간호사의 정답률은 약 40%에 그쳤고, 실무지침의 수행률 역시 60% 수준으로 저조하였다 (Labeau et al, 2009;Plost & Nelson, 2007). (Brown, Wickline, Ecoff, & Glaser, 2009;Oh, 2008). 특히 임상적으로 복잡한 상황에서의 신속하고 명확한 의사 결정 능력이 요구되는 특수 간호 환경의 중환자실 간호사들에게서 그 수행의 어려움이 보 다 높은 것으로 보고되고 있다 (Oh, 2008;Pirret, 2007).…”
Section: 실제로 감염관리를 위해서 중환자실 간호사 교육을 포함한unclassified